2017
DOI: 10.1039/c7py00140a
|View full text |Cite
|
Sign up to set email alerts
|

Model studies of the sequential and simultaneous statistical modification of dendritic functional groups and their implications within complex polymer architecture synthesis

Abstract: Accurate analysis of model systems by MALDI-TOF has established the diversity of structures formed during post-synthesis functionalisation of complex polymer architectures. NMR studies alone are shown to be highly misleading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Dithiocarbonates (xanthates) offer an efficient protecting group chemistry for thiols, they can be synthesized without difficulty and readily undergo deprotection in the presence of primary amines under ambient conditions . We have recently reported the use of xanthates as thiol protecting groups for the synthesis and surface group modification of low generation thiol‐functional dendrimers, linear‐dendritic hybrids, and hyper‐branched polydendrons, using a one‐pot deprotection/functionalization strategy . Thiocarbonyl containing compounds, including xanthates, dithiobenzoates, dithiocarbamates and trithiocarbonates, are commonly used to provide control within reversible addition/fragmentation chain transfer (RAFT or MADIX) polymerization .…”
Section: Figurementioning
confidence: 99%
“…Dithiocarbonates (xanthates) offer an efficient protecting group chemistry for thiols, they can be synthesized without difficulty and readily undergo deprotection in the presence of primary amines under ambient conditions . We have recently reported the use of xanthates as thiol protecting groups for the synthesis and surface group modification of low generation thiol‐functional dendrimers, linear‐dendritic hybrids, and hyper‐branched polydendrons, using a one‐pot deprotection/functionalization strategy . Thiocarbonyl containing compounds, including xanthates, dithiobenzoates, dithiocarbamates and trithiocarbonates, are commonly used to provide control within reversible addition/fragmentation chain transfer (RAFT or MADIX) polymerization .…”
Section: Figurementioning
confidence: 99%
“…26 The mixing of differing monovinyl monomer chemistries within the primary chains of the complex polymer architectures 27,28 has also been used to introduce main-chain functionality; 22,23 however, the joining together of polymer chains via this approach opens a unique opportunity to also control chain-end functionality, as demonstrated by our group in the formation of hyperbranched-polydendrons with varying combinations of dendritic and polyethylene glycol (PEG) chains. [29][30][31] As mentioned above, we have recently reported the formation and application of branched copolymers consisting of OEGMA (M n ¼ 300 g mol À1 ) and EGDMA, initiated by dodecyl a-bromoisobutyrate, 1 (Dod-Br, Scheme 1), under atom transfer radical polymerisation (ATRP) conditions, as highly efficient polymeric surfactants; the copolymers contain a hydrophobic dodecyl group at every chain-end. 24 We hypothesised that initiating this copolymerisation with mixed initiator feedstocks would allow the creation of branched copolymers with varying chain-end composition; however, the decrease in hydrophobic chain-ends may potentially impair the surfactant behaviour of the branched copolymers.…”
Section: Resultsmentioning
confidence: 99%
“…The functional-emulsions initially envisaged for these studies require biologically/pharmacologically-relevant oil phases to be stabilised in water. As such, and building on our recent reports, 24,31 emulsions were generated using the naturally occurring polyunsaturated liquid hydrocarbon squalene using the thiol-functional branched copolymers. This more detailed study was limited to [SH 0.75 /Dod 0.25 ]-p(OEGMA 50 -co-EGDMA 0.80 ) due to its balance of high thiol content, a predicted efficient number of Dod chain-ends to maintain emulsication performance, a good balance of molecular weight, and a weight fraction of highly branched chains representing a high probability of thiol content (8 wt% $ 19 chains; 4 wt% $ 28 chains; and 2 wt% $ 37 conjoined chains) (ESI, Table S6…”
Section: Emulsication and Mucus-responsive Studies Using Thiolfunctional To Branched Copolymer Stabilisersmentioning
confidence: 99%
“…Our previous reports of hyp -PDs have largely relied upon hydrophobic monomers such as 2-hydroxy propyl methacrylate (HPMA), 30 n -butyl methacrylate 31 and t -butyl methacrylate ( t BuMA) 27 to encourage nanoprecipitation of the resulting materials. Copper catalysed atom transfer radical polymerisation (ATRP) has been successfully employed to generate hyp -PDs after the formation and use of tertiary-bromide functional dendron initiators; pH-responsive behaviour has only previously been studied using hydrophobic monomers and tertiary-amine functional dendron initiators such as the second generation (G 2 ) dendron initiator, 1, employed here ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting copolymers, named hyperbranched-polydendrons (hyp-PDs), have a complex architecture of large numbers of conjoined chains with ideally-branched, highly functional dendron chain ends. [26][27][28] We have shown that despite the broad dispersity (Đ) of hyp-PDs, self-assembly under ash nanoprecipitation conditions rapidly generates highly uniform nanoparticles that bear dendron functionality at the surface; the process is mediated by the very high molecular weight component of the molecular weight distribution. 29 In all examples of hyp-PDs to date, hydrophobic monomers have comprised the primary polymer chains of the branched polymer structure, although dendrons of varying functionality and scaffold chemistry have been utilised.…”
Section: Introductionmentioning
confidence: 99%